Some applications of oscillation criteria for fractional differential and difference equations - Chengyuan Yu; Qinghua Feng (IJRDO -JOURNAL OF MATHEMATICS, 2019)
In this paper, we present some applications of oscillation criteria for fractional differential and difference equations. The presented examples consist of both continuous and discrete analysis as special cases.